Managing the team communication of political leaders - Augustinaitis, Arūnas (Politologija, 1999)
Today, the problem of political leadership is, in fact, an actualized aspect which sets ground for identifying the changing political tendencies and realities in the contemporary world. In this given post-industrial context, to answer what the political leader and his team are, means to corroborate several vital issues in the field of political science at once: starting from the prerequisites for organizing and managing the policy, then passing to the characteristics of both the political interests and the means of political activity, communicative mechanisms for elite segmentation, and ending with the most important - the expressions illustrating the postmodern discourse in the field of political sciences. In this respect, the problemacy of the political leader is fairly favorable as long as it focuses on the key issues of contemporary political science and permits to elucidate the most characteristic features of political schism at once.The problem, which regards the political leader and his team, can be solved in two ways:The one which is traditional to political sciences, when the leader is treated as a representative of an organized political force, who is engaged in terms of the programmed doctrine and who is contingent with respect to ideological, political, and propagandist provisions;Postmodern, or (it is almost identical) communicative, standpoint, when the political leader and his team are treated unconventionally, first of all, in terms of competitive organization that renders the services of political activity.Postmodern paradigm of politics matures from communicative and informative changes in the existence of the society when the priorities of creating and practicing information resources come to prevail in the economic field, when the political activity is growingly termed by communicative structures, which inveigle virtually every social strata into the communal "turnover." In this place, we may speak of the concepts which are still quite unusual to the political ear: needs of politics, services of politics, and consumption of politics.The needs of politics can be defined as a type of public need justified by communicative structures, which manifest the political interests and activity of the consumers and mold the corresponding type of service, which can be exposed via a wide range of political behavior and action starting from classical elections and ending with the "participation" and "pressure" through the media, direct talks, contacts on telecommunicative nets, or the usual consumption of political information.With respect to this, the political activity may now on be interpreted from the position of modern theories of organization, among which the concepts of organizational communication and communication management, which have attained a universal character in relation to nearly each realm of the information society, dominate.In circumstances when almost the entire society (on state, regional, or even global scale) turns into political consumers and actors, social and ideological engagement is not the most important substance (i.e., division between left-right becomes real on the basis of values, not ideological position, alone). It comes to be countervailed by the competitiveness of the political activity itself. Nowadays, most probably, we can speak of a political consumer as a mass type, which, in fact, coincides with the consumption of mass and specific communication.Gradually, the parties evolve into administrative mechanisms, which adapt themselves to an expanded and invigorated political market. In this respect, mass media and other communicative structures and instruments become but sole means for political activity, safeguarding its inter-relationship with various social strata and interest groups. Thus, the maneuvers of a political team are increasingly identified with the practice of public relations oriented at the political needs.First of all, it should be emphasized that communicative ties fill the formal positions up, and implement them. There is a very close inter-relationship between the formal and information positions. Furthermore, the quality of the functioning of formal structures, plus, the optimization of organization depends upon the factors of information.As usual, the communicative system of the political team emerges as an outcome of some sort of competition - both, internal and external - and the rules characteristic to it. Communicative system of this sort of "competitive coexistence" sets a favorable ground for the emergence of the rules for identification of the team, as well as the system of strategic planning and preparation for substitution. Habitually, these rules alter but a little that allows, first, the maintenance of a relatively stable staff organization, and second, forges a long-term policy of ends.Within the staff, there is a communicative division of competence, which can be clear and chaotic, as well as formal and casual. It is the association of these competencies alone that make it possible to converse the team as such. Herein, in the face of concrete information relationships, where the freedom of movement is restrained by the rules and some behavioral model is expected, likewise in chess play - the pieces, we may propound a communicative legitimization of the competence.In other words, we may speak of the intersection of political and administrative behavior, the intersection which, due the fact that nowadays it has been made dependent on the technologies of information and communication, and the media pressure, becomes increasingly close and stable.
Keywords: -